The Boy Apprenticed to an Enchanter - Colum, Padraic, 1881-1972; Walker, Dugald Stewart, 1883-1937 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Boy Apprenticed to an Enchanter" by Padraic Colum is a fantasy novel written in the early 20th century. The story is set in a mythical past and follows a young boy named Eean, who is fated for an adventure when he becomes an apprentice to a powerful enchanter named Zabulun. As he learns the ways of magic and enchantment, Eean finds himself embroiled in grand tales of danger, mythical creatures, and a quest to retrieve a magical mirror that has the potential to shift the balance of power in Babylon. At the start of the novel, we meet Eean, the son of a poor fisherman, who is approached by an enigmatic stranger from a mysterious brass boat. This stranger offers to take Eean as his apprentice, revealing that he is an enchanter. As his father reluctantly consents, the boy's journey begins, leading him from his familiar shores into a world of enchantment and peril. The narrative introduces King Manus and his prized horses, setting the stage for a tale steeped in mythology. The opening draws the reader into Eean's awe as he embarks on a path that intertwines his fate with the larger powers at play, foreshadowing the trials and adventures that await him in the land of the enchanter. (This is an automatically generated summary.)
Release date is 2016-10-10
E-text prepared by Paul Clark and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Fantasy fiction; Children's stories; Horses -- Juvenile fiction; Magicians -- Juvenile fiction; Apprentices -- Juvenile fiction